Suburbanization in Greece: The informal transformation of Maroussi into the economic hub of Athens - Ioannis Chorianopoulos; Alexandros Karvounis; Dimitris Ballas; Nick Phelps (European Regional Science Association (ERSA), 2013)
Greek cities are a seminal part of the Mediterranean urbanization thesis. Corresponding features include the comparatively belated occurrence of urban in-migration, the particularity of the urban pull factors, and the unplanned nature of urban expansion. The considerable and extensive urbanisation wave note in Greece in the post-war period was part of a wider transformative process, characterized by the shifting economic orientation from a prevailing agrarian sector towards urban-industrial economies. The limited manifestation of internal economies of scale in industrial firms, and the few signs of economies of localisation affecting the spatial pattern of industrial development point to the weight of urbanisation as the major factor in industrialisation. In order to maintain and enhance the urbanization/industrialization process, the authoritarian national leadership of the time eased off regulatory planning controls, tacitly facilitating the rapid yet unordered expansion of cities. The conceptualization of the ensuing urban sprawl as an unsustainable trend occurred decades later, following the country?s return to democracy (1974). The path dependent qualities of urban growth management, however, mitigated the effectiveness of the respective efforts. This paper explores the sprawling tendencies of Greek cities, commenting on the limited ability of the regulatory planning framework to influence and direct urban expansion. The Athenian municipality of Maroussi is used as a case in point. Maroussi was a rural area of the Athenian hinterland, turned gradually into the city?s major economic centre. Fieldwork research in Maroussi underscores the informal qualities of Greek suburbanization. The paper is organized in three. The first part discusses the growth of Greek cities in the post-war years, portraying the popular colonization of peri-urban land. The second part outlines the policy changes introduced since the early 1980s, part of an attempt to delineate urban growth. Key amongst them, the launch of a series of state spatial restructuring reforms, aiming to equip local authorities with the necessary means to control urban sprawl. The third part of the paper looks closely at Maroussi, mapping the process and discussing the consequences of an urban expansion mode based on unhindered market forces and unregulated private initiative.
Keywords: R11; R28; R38; R52; 330; Mediterranean city; suburbanization; urban planning; popular colonization; informality